Experimental studies on ferrofluid pool boiling in the presence of external magnetic force - ÖZDEMİR, MEHMED RAFET (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
The past decade has witnessed rapid advances in thermal-fluid applications involving nanoparticles due to existing heat transfer enhancements. The main challenges in working with nanoparticles are clustering, sedimentation and instability encountered in many studies. In this study, magnetically actuated Fe3O4 nanoparticles were coated with a fatty acid and dispersed inside a base fluid (water) in order to avoid clustering, sedimentation and instability as well as to improve the thermal performance. Boiling heat transfer characteristics of the ferrofluids were experimentally investigated with magnetic actuation and compared to the results without magnetic actuation. Nanoparticle mass fraction was the major parameter. Boiling heat transfer coefficient of the magnetically actuated system was found to be significantly higher compared to the case without magnetic actuation. The results showed that boiling heat transfer coefficient was not sensitive to the nanoparticle mass fraction.
Keywords: Nanofluids; Magnetic field; Pool boiling; Magnetic nanoparticle; Boiling heat transfer; Magnetic actuation; HEAT-TRANSFER ENHANCEMENT; THERMAL-CONDUCTIVITY; NATURAL-CONVECTION; COOLING SYSTEMS; NANOFLUID; FLOW; NANOPARTICLES; TEMPERATURE; FRACTION; AL2O3